Response to Intervention and Identifying Reading Disability - Hoang, Thienhuong (Journal of the American Academy of Special Education Professionals, 2010)
The educational community is discussing response-to-intervention (RTI) as an alternative assessment method. This study investigates assessment elements (beginning text level, ending text level, and number of weeks’ participation) of the Reading Recovery (RR) program as part of a future RTI model. By means of a discriminant function analysis, third to fifth grade students (N = 155) who participated in RR during first grade formed the basis of the data for the analysis. The results indicated that RR assessment elements are significant predictors of first-grade students who are later identified as having a reading disability. Ending text level was consistently the largest predictor of students later classified as having a reading disability or not.